Od priprave na branje do bralnega razumevanja - Potočnik, Nataša (Šolska knjižnica, 2012)
The understanding of the reading process as well as the steps in reading development is essential for optimal development of reading literacy in school. The paper summarizes the fundamental elements in the development of literacy thus showing which process take plece in reading, how to develop the foundations of early literacy, which (pre)literacy skills need to be developed and how to logically upgrade the level of reading technique using reading learning strategies. It also deals with the wholistic teaching of reading and touches on the issue of ensuring equal opportunities for all pupils.
Keywords: bralna pismenost; bralne tehnike; branje; razumevanje